Moulding self esteem in Nigerian university undergraduates (2009)
Researches on Higher Education in Nigeria have been focusing mostly on the problems of finance, efficiency equity, quality and governance. Besides these issues of financing and equity, moral quality of university graduate is an issue that should bother parents and lecturers who are involved indirectly and directly in University system. This study investigates the effect of self esteem on undergraduates anti suggests way s of moulding their self esteem for learning outcomes that University . duration should produce in developing countries.